Increasing Children's Self-Confidence through Parenting: Management Perspective - Sarkowi Sarkowi; Faizatul Widat; Nur Ima'atul wadifah; Desy Rohmatika (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2023)
A person's self-confidence level is different; in essence, every human being is created to have self-confidence, but self-confidence is different from one another. Some grow and develop from birth, but some are obtained from several factors, such as parenting and environmental stimulation. This study aims to determine the management of parenting methods in growing children's self-confidence. The research method used is a qualitative case study type method. The research results show that; the parenting method in stimulating the development of self-confidence in students is carried out in the following stages: program planning, classification of parenting programs, implementation of parent gathering programs, and program evaluation. The management of the parenting method used turns out to be able to stimulate children's self-confidence optimally because the management is carried out continuously by involving the collaboration of teachers and student guardians; this collaboration is a novelty from previous research and through collaboration makes students more confident, independent and able to adapt to the environment.